Facile synthesis of Ag/ZnO metal–semiconductor hierarchical photocatalyst nanostructures via the galvanic-potential-enhanced hydrothermal method. Issue 46 (31st October 2018) - Shaislamov, Ulugbek; Lee, Heon-Ju
Abstract : Hierarchical metal–semiconductor nanostructures composed of Ag nanowire and ZnO nanorod branches were prepared by using the galvanic-potential-enhanced hydrothermal method. Abstract : Hierarchical metal–semiconductor nanostructures (NSs) composed of a backbone made of Ag nanowire and ZnO nanorod (NR) branches were successfully prepared using the galvanic-potential-enhanced hydrothermal method. A galvanic cell structure was formed between an Al bottle anode that was used as a hydrothermal reactor and an Ag NW cathode dispersed in a hydrothermal solution. As a result, the contact-potential-driven hydrothermal growth of the ZnO NRs on the sidewalls of the Ag NWs could be achieved. The morphological and microstructure characterization confirmed the formation of well-arranged hierarchical NSs composed of Ag NW trunk and ZnO NR branch structures. The photocatalytic properties of the hierarchical Ag/ZnO NSs were investigated by degrading methylene blue (MB) dye as a model pollutant. It was found that the hierarchical Ag/ZnO NSs demonstrated a more than two-fold faster degradation rate than the pristine ZnO NSs. The high-performance photocatalytic activity of the Ag/ZnO hierarchical NSs was attributed to the synergetic effect of the metallic Ag NWs and the ZnO NRs that enhanced the charge separation and diffusion by suppressing charge recombination, as well as enhanced reaction sites and light absorption.